2014
DOI: 10.4217/opr.2014.36.1.039
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Water Temperature and Oxygen Consumption Rate of the Black Scraper Thamnaconus modestus

Abstract: The black scraper Thamnaconus modestus was a commercially important fish species in the 1980s, but suddenly its commercial significance decreased in the 1990s mainly due to continuous overfishing. Recently, in order to reverse the depleted stocks of the black scraper and help the species recover, seed production technology has emerged. This has led to the farming of the black scraper in several parts of the southern coast of Korea. Since detailed research on its metabolism in relation to water temperature has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…WT, dissolved oxygen concentration (DO), and photoperiod are potent influences on feed consumption, metabolic rate and energy expenditure, and thus, on growth of poikilothermic vertebrates, including fish (Dutta, 1994;Elliott, 1982;Hur, 2018;Lee et al, 2014). Therefore, the effects of these environmental factors on fish growth and metabolism warrant thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WT, dissolved oxygen concentration (DO), and photoperiod are potent influences on feed consumption, metabolic rate and energy expenditure, and thus, on growth of poikilothermic vertebrates, including fish (Dutta, 1994;Elliott, 1982;Hur, 2018;Lee et al, 2014). Therefore, the effects of these environmental factors on fish growth and metabolism warrant thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, the WT is an essential factor so that it controls physiological factors; reproduction, nutritional metabolism, growth, etc. Therefore, its rapid variation makes change and break physical condition and homeostasis of fish (Barton & Iwama, 1991;Hur, 2018;Lee et al, 2014;Shin et al, 2018). Therefore, this study was performed to get primary data for repeated acute change of WT.…”
Section: Introductionmentioning
confidence: 99%
“…Water temperature (WT), dissolved oxygen (DO) concentration, and photoperiod influence feed consumption, metabolic rate, and energy expenditure, and thus effect the growth of poi-kilothermic vertebrates, including fish (Lee et al, 2014;Liyanage et al, 2018;Shin et al, 2018). Therefore, the effects of these environmental factors on fish growth and metabolism warrant thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have demonstrated effects of various factors such as WT, salinity, photoperiod, fish size, feed amount, and stress on oxygen requirements of fish (Forsberg, 1994;Lee et al, 2014;Shin et al, 2018;Wei et al, 2019). In particular, in the case of aquaculture, DO content is considered an important factor for determining carrying capacity and production (Jørgensen et al, 1991;Lee et al, 2014;Shin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation